2013
DOI: 10.1155/2013/953974
|View full text |Cite
|
Sign up to set email alerts
|

The Associated Ion between the VDR Gene Polymorphisms and Susceptibility to Hepatocellular Carcinoma and the Clinicopathological Features in Subjects Infected with HBV

Abstract: Aim. To evaluate the possible association between the vitamin D receptor (VDR), single-nucleotide polymorphisms (SNPs), and hepatocellular carcinoma (HCC) in patients with chronic hepatitis B virus (HBV) infection. Method. 968 chronic HBV infection patients were enrolled, of which 436 patients were diagnosed HCC patients, and 532 were non-HCC patients. The clinicopathological characteristics of HCC were evaluated. The genotypes of VDR gene at FokI, BsmI, ApaI, and TaqI were determined. Results. The genotype fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 31 publications
2
30
1
Order By: Relevance
“…A total number of 198 articles were identified in the electronic search in foreign databases such as PubMed/Medline, EMBASE, and Cochrane Library, and Chinese databases such as CNKI, VIP, Wanfang Data, and SINOMED (Figure 1). Three studies from 2013 to 2016 were finally included in our analysis (25)(26)(27). The numbers of HCC cases and controls were 728 and 920, respectively (Table 1).…”
Section: Search Results and Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A total number of 198 articles were identified in the electronic search in foreign databases such as PubMed/Medline, EMBASE, and Cochrane Library, and Chinese databases such as CNKI, VIP, Wanfang Data, and SINOMED (Figure 1). Three studies from 2013 to 2016 were finally included in our analysis (25)(26)(27). The numbers of HCC cases and controls were 728 and 920, respectively (Table 1).…”
Section: Search Results and Included Studiesmentioning
confidence: 99%
“…To find out new prevention methods, possible mechanisms, and potential advanced therapies, we need to have a deeper understanding of the mutual interaction between VDR polymorphism and HCC. So far, there are several articles that have drawn our attention (25)(26)(27). However, the results have not been integrated yet; thus, we conducted a metaanalysis to give a more objective and compelling answer.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from population studies suggests that vitamin D deficiency is highly prevalent among the general population in China, which may be related to genetic variation in VDR [16]. Previous studies have shown that VDR genetic variants (such as rs1544410, rs7975232 and rs731236) can participate in the development of various tumors (such as prostate cancer and hepatocellular carcinoma) by affecting the biological effects of vitamin D [17,18]. Shortly thereafter, vitamin D deficiency was found to be associated to immune-related diseases (systemic lupus erythematosus) and infectious diseases (tuberculosis) [19].…”
Section: Discussionmentioning
confidence: 99%
“…This polymorphism leads to a T>C (threonine to cysteine) substitution and the generation of a protein shortened by three amino acids, which makes the protein less functionally active than the wild type (van Etten et al 2007). This polymorphism has been implicated in the response to PEG-IFN therapy and several chronic liver diseases including autoimmune hepatitis and HCC in patients with chronic HBV infection (Mostafa-Hedeab et al 2018;Vogel et al 2002;Yao et al 2013). The present study found an association between the FokI polymorphism and advanced liver fibrosis in patients with chronic HCV infection.…”
Section: Discussionmentioning
confidence: 99%